A tira no livro didático: texto ou pretexto ? - Andrade, Sandra Helena de (2009)
This Master's degree dissertation aims at analysing how Portuguese language textbooks (PLT) use multimodal genres, in particular the newspaper comic strip, investigating whether the genre is used taking into consideration their semantic-discourse and pragmatic aspects or if it is used only as an excuse for grammatical analysis. The text research, which was of qualitative-interpretative in nature, attempts to answer the following questions: 1) How was the newspaper comic strip genre dealt with in the Portuguese language textbook, as text or as pretext?; 2) Is there guidance given to the teacher on dealing with multimodal texts in the PLT?; 3) Do the suggested activities in the textbook for the comic strips lead the learner to a critical reading of all the semiotic modes in the text (verbal and non-verbal)? and 4) What concepts of language are presented in the heading of the activities suggested by the authors? The corpus of our analysis was a collection of textbooks from the 5th to the 8th grade of elementary school (3rd and 4th cycles), recommended by the Ministry of Education in the 2008 National Textbook Programme (PNLD/08) Portuguese: Language by Willian Roberto Cereja and Thereza Cochar Magalhães. In order to do that, we traced the historical concept of the genre in Rhetoric, Poetry and Linguistics, from Bakhtin (2006 [1992]), Marcuschi (2005, 2006, 2008), in the Bazerman's (2005) concept of genre as social action and we followed the socio-interactionist perspective outlined in the works of Bronckart (2003), Dolz and Schneuwly (2007) who take the genre concept of Bakhtin, granting it a place of relevance in language teaching. Our analysis allowed us to verify that comic strips appear in every single chapter in the PLT and has great pedagogic potential for they are constituted of true socio-communicative formats. However, they are presented in a mutilated manner and, in the activities in which they are used, it is not the socio-discursive characteristics of the genre which are used. That is, 70.91% of the comic strips in the activities of the PLT in question are used as pretext for grammar and spelling exercises, which leads us to conclude that, in relation to the treatment given to this genre, the PLT adopts traditional conception of language teaching.